Waktu tunggu pelayanan resep rawat jalan di instalasi farmasi Puskesmas Purbolinggo sebagai indikator standar pelayanan minimal puskesmas - Saputri, Gusti Ayu Rai; Nurhayati, Robby Candra (JOURNAL OF Pharmacy and Tropical Issues, 2023)
Background: Community health center prescription services are a supporting factor for quality health services. In addition, public health center prescription services are the minimum standard for pharmaceutical services. The achievement of definite results to improve the quality of life of patients with direct and responsible care to patients related to pharmaceutical preparations is the meaning of pharmaceutical services. Indonesia itself has regulated it in State Law Number 36 of 2009 concerning Health, which explains that pharmaceutical practice includes coaching including quality control of pharmaceutical availability, protection, supply, storage and distribution of drugs, means of delivering drugs based on doctor's prescriptions, drug explanations. service and not to be missed. also the distribution of drugs, modern medicinal ingredients and traditional medicines must be carried out by health workers who have the knowledge and skills under the regulations determined by law. Purpose: To determine the average waiting time for outpatient prescription services at the pharmacy installation of the Purbolinggo Community Health Center. Method: Collecting data through observation with patient variables, patient days of treatment, length of prescription, screening and diagnosis of prescriptions, labeling, drug packaging, drug delivery, and total length of prescription service time in minutes. Results: The average waiting time required to complete a prescription is 9.10 minutes and to complete a finished drug prescription is 2.56 minutes. Conclusion: The waiting time for prescription services has met the minimum service standards, namely 30 minutes of non-concoction recipes and 60 minutes of concoction recipes.   Keywords: Waiting Time; Outpatient Prescription Services; Community Health centers   Pendahuluan: Pelayanan resep puskesmas merupakan faktor penunjang pelayanan kesehatan yang bermutu. Selain itu pelayanan resep puskesmas menjadi standar minimal pelayanan Kefarmasian. Mencapai hasil pasti untuk meningkatkan kualitas hidup pasien dengan pelayanan langsung dan bertanggung jawab kepada pasien terkait sediaan farmasi merupakan arti dari pelayanan Kefarmasian. Indonesia sendiri sudah mengaturnya pada Undang-undang Negara Nomor 36 Tahun 2009, tentang Kesehatan menjelaskan bahwa praktek kefarmasiaan meliputi pembentukan termasuk pengawasan mutu kesediaan farmasi, proteksi, pemasokan, restensi dan pengedaran obat, fasilitas pemberian obat berdasarkan resep dokter, pelayanan penjelasan obat dan tidak ketinggalan pula pembentangan obat, bahan obat moderen dan obat tradisional harus dikerjakan oleh tenaga kesehatan yang memiliki keilmuan dan adikara sesuai dengan ketentuan peraturan yang di tentukan undang-undang. Tujuan: Untuk mengetahui rata-rata waktu tunggu pelayanan resep rawat jalan di instalasi farmasi Puskesmas Purbolinggo. Metode: Pengumpulan data melalui observasi dengan variabel seorang pasien, hari pasien berobat, durasi waktu pemberian resep, skrining dan diagnosa resep, pemberian etiket, pengemasan obat, penyerahan obat, serta total aktu durasi pelayanan resep dalam itungan menit. Hasil: Rata-rata  waktu  tunggu  yang  dibutuhkan  untuk  menyelesaikan  resep racikan adalah 9,10 menit dan untuk menyelesaikan resep obat jadi adalah 2,56 menit. Simpulan: Waktu tunggu pelayanan resep sudah memenuhi standar pelayanan minimal yaitu resep non racikan 30 menit dan resep racikan 60 menit.   Kata kunci : Waktu Tunggu; Pelayanan Resep Rawat Jalan; Puskesmas.